Reducing chemical oxygen demand and decolorization of direct dye from synthetic-textile wastewater by ozonization in a batch bubble column reactor - Turhan, Kadir; Turgut, Zuhal (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2007)
Decolorization of wastewater containing direct dye (Sirius Red F3B) by ozonization was studied in an attempt to abate pollution caused by textile dyeing houses and dyeproducing plants. The decolorization process of the direct dye was carried out by bubbling ozone at the bottom of a bubble column reactor containing the dye solution. The effect of dye concentration, ozone dose, ozone-air flow rate and solution-pH on the rate of decolorization was studied. Additionally it was shown that the ozone method is effective for the reduction of COD as well as for the decolorization of dyestuff wastewater, to present the optimum conditions for dyestuff wastewater treatment. The reaction rate was followed by measuring the dye concentration at different times of the decolorization process. The rate of dye oxidation was found to increase with increasing ozone concentration in the air-ozone mixture, but decreased with increasing dye concentration. The rate of dye oxidation increased with increasing air-ozone flow rate and solution-pH, reached a maximum, and then decreased with a further increase in air-ozone flow rate. The results with the direct dyestuff wastewater showed that COD reduction and decolorization were remarkable under basic conditions (pH 12). A large amount of bubbles was formed at high ozone-air flow rate. High ozone concentration was effective for the reduction of COD. After 24 min of ozone treatment, decolorization was complete. From these results, the ozone treatment of the dyestuff wastewater in both COD reduction and decolorization was excellent.
Keywords: ozone; Sirius F3B; wastewater treatments; decolorization; Direct Red 80; COD; OZONATION; OZONOLYSIS; COLOR; Environmental Sciences & Ecology